The Role of Polar Functional Groups of the Special Pair on the Excites States in Terms of the Dielectric Environment: Screened Range Separated Time-Dependent Density Functional Theory - Zühra Güneş; Murat Ertürk; Fehime Hayal Geçit; Hüseyin Aksu (Journal of Advanced Research in Natural and Applied Sciences)
We study the role of polar functional groups (PFGs) on the excited states and the changes of net charges on the charge transfer (CT) states in terms of dielectric constant using ab initio theory. It is found that the PFGs play a dielectric medium in which the side PFGs interact strongly with the incoming light, and this interaction contributes to the wave function of excited states. Results reveal that conformer structure due to side groups has more influence on transition dipole moment (TDM) and thus on the electronic excitations. We have also discussed the well-known J- and H- aggregation physical phenomenon for the special pair and shown the excitonic splitting energies of the special pair compared to the monomer's first excited state energies. Excitation energies, oscillator strength, and CT states are obtained by using time-dependent density functional theory (TDDFT) and accompanying screened range-separated hybrid functionals (SRSH) in which comparisons are made with $ω$B97X-D functional.